Risks of Fraud in CTP in Siberia: Causes, Consequences, Regulation - E. L. Prokopjeva; L. Yu. Lysova (Финансы: теория и практика, 2025)
The problem of unfair actions in Compulsory Third Party (CTP) has persisted in Siberia for several years and, first of all, is related to fraud. The purpose of the study is to assess the causes and impact of the risks of unfair actions in the field of CTP on the insurance market using the example of the regions of Siberia. The research methodology includes dynamic, spatial and correlation analysis, as well as index and coefficient methods used to assess the total risk. The article analyzes the quantitative indicators of the risk of unfair actions in the field of CTP in the regions of Siberia, identifies the causes of the unfavorable situation, the consequences of a socio-economic nature, and provides proposals aimed at reducing the risk. To improve the efficiency and quality of services in the CTP market, it is necessary to assess the factors constraining its development, regularly conduct communication activities between government authorities and the insurance business, differentiate quantitative indicators when assessing damage taking into account regional specifics, develop an insurance culture and accessibility of CTP services in remote areas. The study will be useful for regulatory authorities and organizations of the insurance market, executive authorities at the federal and regional levels, and individual subjects of the insurance market in the development of regional insurance policy.